Ownership structure and capital structure dynamics in South African firms - Delane Naidu (South African Journal of Economic and Management Sciences, 2024)
Background: The ownership structure can impact capital structure decisions as owners are an influential group that govern the financial decisions of firms. Hence, the ownership structure and the categories of its owners have important implications for the capital structure of firms.